2019
DOI: 10.1016/j.jrurstud.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Out of love for the village? How general and selective forms of attachment to the village explain volunteering in Dutch community life

Abstract: In the past century, the increasing scale of daily life has weakened and changed the ways residents feel attached to their village. A general and all-encompassing village attachment has evolved into less involving, more selective and partial forms of attachment. Concerns have been raised as to whether these changing forms affect volunteering in village life. In this paper we distinguish between general and selective forms of attachment to the village-social, cultural and environmental attachment-and explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 52 publications
0
16
0
5
Order By: Relevance
“…Often, in these cases, the lines are drawn based on residence frequency (permanent or summer resident) or residence history (in-migrant or in-born). In several studies, in-migrants (or incomers), second home-owners and 'native' inhabitants are separated as different groups within a community (Ellingsen, 2017;Gieling et al, 2019). Our data show that these distinctions were really ambiguous, and the notion of a 'native' resident and incomer was fluid.…”
Section: Paradoxes Of Representations Of the 'Rural' And 'Community'mentioning
confidence: 66%
See 1 more Smart Citation
“…Often, in these cases, the lines are drawn based on residence frequency (permanent or summer resident) or residence history (in-migrant or in-born). In several studies, in-migrants (or incomers), second home-owners and 'native' inhabitants are separated as different groups within a community (Ellingsen, 2017;Gieling et al, 2019). Our data show that these distinctions were really ambiguous, and the notion of a 'native' resident and incomer was fluid.…”
Section: Paradoxes Of Representations Of the 'Rural' And 'Community'mentioning
confidence: 66%
“…(Bossuet, 2006;Granovetter, 1973). The vision of how to (re)arrange local cultural and symbolic meanings and materialities of the area may be a kind of place branding (Argent, 2019, p. 759), which invites new meanings that attract new inhabitants to the region (Gieling et al, 2019). These aspects illustrate the paradox well.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in more peripheral rural areas with low population densities and declining populations that are located relatively far away from larger cities, the loss of facilities has a strong impact on the villages and their inhabitants. Here, rural residents have fewer alternative facilities available and often they are only available at large distances from their homes (Gieling et al., 2019a; Manthorpe & Livsey, 2009; Shucksmith et al., 2009). In the more densely populated and highly urbanised rural areas in Western Europe, such as The Netherlands, alternative facilities often are available relatively close by and most rural residents are no longer dependent on local facilities because they have access to (car) mobility.…”
Section: Place Meanings and The Loss Of Local Facilitiesmentioning
confidence: 99%
“…Furthermore, Walton and Cohen (), Walton et al () and Gieling et al () found that the sense of social belonging that results from positive and enduring social relationships motivates and enables residents to engage in community‐focused activities. Residents who feel socially embedded in their community have more access to information about collective wishes and needs, which supports community engagement (Brennan and Luloff ; Crona and Bodin ; Walton and Cohen ; Walton et al ).…”
Section: Non‐engagement Of Residents In Civic Initiatives In Rural Dementioning
confidence: 99%